Modelling the Measurement of Engagement Index of the Regional Governments' Social Media in Indonesia - Rosyid Abdillah; Nur Aini Rakhmawati (JOIN (Jurnal Online Informatika), 2020)
Several types of engagement index and its variables can predict the engagement index of social media. However, no research has yet to use Structural Equation Modelling to model the engagement index of the variables from the prior researchers. This study was conducted to test the metrics of social media including like, comment, share and reply towards the online engagement variables that are measured by its affective engagement, cognitive engagement and behavioural engagement. The results indicate that the reply from the admin variable is the most significant factor in creating engagement on the social media of the Local Governments in Indonesia. This will then be used to increase the engagement index of the local governments in Indonesia.